Phenolic Constituents of Vaccinium Species from Both Natural Resources and Micropropagated Plantlets - Mustafa Cüce; Tuba Bekircan; Atalay Sökmen (International Journal of Secondary Metabolite)
Fruits and leaves of Vaccinium species have rich bioactive phytochemicals. These bioactive phytochemicals make these plants particularly valuable for the medical and food industry. This novel approach was designed to determine the phenolic content of Vaccinium species obtained from both micropropagated and naturally growing leaves. An efficient micropropagation protocol was developed to produce tree Vaccinium species plantlets via direct organogenesis. Lateral buds containing one or two leaves were cultured in McCown woody plant medium (WPM), supplemented with zeatin/indole-3-butyric acid (IBA) (1.0/0.1 mg L–1). In conclusion, Protocatechuic acid, Chlorogenic acid, Syringic acid and Routine phenolic compounds were determined in significant amounts. It has been determined that the phenolic compounds of leaves produced in tissue cultures is higher than the phenolic compounds obtained from naturally growing leaves.